Teaching programming in higher education: a bibliometric analysis of trends, technologies, and pedagogical approaches - Vinueza-Morales, Mariuxi; Rodas-Silva, Jorge; Vidal-Silva, Cristian; Córdova-Morán, Jorge; Cevallos-Ayón, Edwin (Frontiers in Education, 2025)
The continuous evolution of digital technologies has significantly reshaped the landscape of higher education, particularly in programming instruction. As programming skills become increasingly essential across multiple disciplines, analyzing the research trends, key contributors, and institutional impact on programming education is crucial. This study presents a bibliometric analysis to identify influential research works, leading authors, and major institutions that have shaped this field over the years. By systematically examining scholarly publications, this study explores the most recurrent pedagogical approaches, the role of emerging technologies, and the methodological frameworks used to assess programming competencies. Additionally, it highlights prevailing research trends, knowledge gaps, and future directions for improving programming education in higher education institutions. The findings of this work will support educators, curriculum designers, and policymakers in refining instructional strategies, fostering innovative learning environments, and aligning academic programs with industry demands.